1999
DOI: 10.1046/j.1442-2042.1999.06128.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile function and nocturnal penile tumescence in patients with prostate cancer undergoing luteinizing hormone‐releasing hormone agonist therapy

Abstract: Background: Luteinizing hormone-releasing hormone (LHRH) agonists have been widely used as effective agents in endocrine therapy for prostate cancer. Continuous administration of the drug results in profound suppression of testicular androgen production. However, the side effects on erectile function have not been fully investigated. Methods:We studied the influences of testosterone suppression on male sexual function and nocturnal penile tumescence in nine sexually active patients with prostate cancer who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 12 publications
2
32
0
1
Order By: Relevance
“…In the study by Marumo et al 50 the maximal circumferential increase at the tip and base of the penile shaft during erection was significantly decreased by the administration of LHRH agonist (P,0.01). This is likely the result of smooth muscle loss and collagenization of the corporal tissue with resultant penile contraction.…”
Section: Penile Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Marumo et al 50 the maximal circumferential increase at the tip and base of the penile shaft during erection was significantly decreased by the administration of LHRH agonist (P,0.01). This is likely the result of smooth muscle loss and collagenization of the corporal tissue with resultant penile contraction.…”
Section: Penile Morphologymentioning
confidence: 99%
“…49 In this study, 51% of men interested in sex before treatment reported 'no interest' after therapy and about 73% reported ceasing engaging in sexual activity after treatment, regardless of the type of ADT prescribed. 49 In the study by Marumo et al, 50 despite the total suppression of sexual activity induced by the LHRH agonist treatment, none of the nine previously active sexual patients presented serious complaints concerning ED and total suppression of sexual activity. This was explained by a concomitant selfreported decrease in sexual desire following therapy in all patients.…”
Section: Sexual Desirementioning
confidence: 99%
See 1 more Smart Citation
“…An objective measurement of nocturnal penile tumescence prior to LHRH agonist therapy and 4 and 12 weeks after treatment showed a statistically significant decrease in frequency, magnitude, duration, and rigidity of nocturnal erections. The men in that study also reported decreased sexual desire, interest, and frequency of intercourse [141].…”
Section: Sexual Dysfunctionmentioning
confidence: 83%
“…One study also showed that there is a decrease in frequency, degree of erection, length of erection, and rigidity in objective measurement of nocturnal penile tumescence before and after starting LHRH analog therapy. This study also showed a decrease in libido and frequency of intercourse [65]. Erectile dysfunction also is a common problem in men without prostate cancer.…”
Section: Sexual Dysfunctionmentioning
confidence: 92%